The ISM local to the runaway star WR16. Issue 1 (30th April 2020) - Cichowolski, S; Duronea, N U; Suad, L A; Reynoso, E M; Noriega-Crespo, A; Bronfman, L
ABSTRACT: Massive stars leave their imprint on the interstellar medium as they radiate their energy and undergo episodes of mass ejection throughout their lives. In this paper, we analyse the case of the Wolf–Rayet star WR16 combining archival multiwavelength data with new molecular observations obtained with the Atacama Submillimeter Telescope Experiment (ASTE). Our results suggest that during the main-sequence phase, WR16 swept up the surrounding gas creating a molecular structure (which we call Component 1) which also contains very cold dust observed in the infrared band. In a subsequent stage of evolution, as an LBV, the star underwent mass eruptions that were later overrun by the fast winds of the current WR phase. The final result is the round nebula revealed by the optical and IR images, and the molecular clumps detected. We have also computed the peculiar velocity of WR16 using Gaia data and, accordingly, confirm it as a runaway star. We propose that several features observed in different wavelengths can be explained under a bow-shock scenario linked to the high velocity of WR16.